Adrenalectomies in a department of general surgery - Comodo, Oriana B.; Frías Mena, Guadalupe; du Plessis, M. Cristina; Ferrari Poderoso, Ana C.; Vidal Carcamo, Franco E.; Guatelli Casiva, Juan I.; Varela, José R.; Petracchi, Enrique J. (Revista Argentina de Cirugía, 2026)
Background: Adrenal tumors account for 0.6 to 1.5% of all abdominal neoplasms. The evaluation of adrenal tumors requires specific imaging tests, clinical evaluation, and endocrine workup. Laparoscopic adrenalectomy is the preferred technique. Objective: The aim of this study was to describe the results of laparoscopic adrenalectomies performed in a general surgery department for the treatment of adrenal gland disease. Material and methods: We conducted an observational, descriptive and retrospective study of patients undergoing surgery between January 2014 and April 2025. Results: A total of 15 patients were included; mean age was 58.5 years (SD 15.6), and 9 (60%) were women. The preoperative diagnosis was made by clinical evaluation in 7 cases (46.7%), during cancer workups in 4 cases (26.7%), and incidentally in 4 cases (26.7%). The surgical approach was performed using transperitoneal laparoscopic technique. Conversion to open surgery was necessary in 1 patient (6.7%). Mean operative time was 183.6 minutes (SD 51.3). There were 2 complications (13.3%), both grade 4a of the Clavien-Dindo classification. Mean hospital length of stay was 5 days (range: 2-30). The pathology reports documented 5 cases (33.5%) of pheochromocytoma, 3 cases (20%) of adrenal cortical adenoma, 2 cases (13.3%) of metastasis, and 5 cases (33.5%) of other diagnoses. Conclusion: Most diagnoses were made during clinical evaluation or cancer workups, and the transperitoneal laparoscopic approach was a safe option with an acceptable conversion rate (6.7%) and favorable postoperative outcomes.